Primary pericardial mesothelioma presenting as pericardial constriction - Ansari, MA; Thapa, R.; Pradhan, S. (Journal of Institute of Medicine Nepal, 2011)
A 48 year-old-male presented with a six month history of shortness of breath and cough with low grade fever. Chest x-ray shows enlarged cardiac size. Echocardiogram revealed pericardial effusion. ESR was raised and blood count showed lymphocytosis. Anti-tubercular treatment was started and four months after completion of treatment there was no significant improvement. Pericardial biopsy was done which revealed findings of chronic pericarditis. Echocardiogram was repeated which revealed thickened pericardium with few foci of calcification and pericardial effusion. Diagnosis of constrictive pericarditis was made. Patient was planned for pericardiactomy. During operation fleshy vascular mass was seen arising from pericardium along with nodular pericardial thickening. Biopsy was taken and closer was done. Post operatively contrast enhanced CT scan of chest was done which revealed malignant mesothelioma. Histopathological analysis showed a primary malignant mesothelioma. Post operative period was uneventful for initial 2-3 days. Patient was taken by his party against medical advice on 3rd post-operative day. Patient did not returned to the hospital again.